2021
DOI: 10.3920/cep200073
|View full text |Cite
|
Sign up to set email alerts
|

A narrative review of the risk factors and psychological consequences of injury in horseracing stable staff

Abstract: Horseracing stable staff have a multifaceted role, acting as care givers, skilled athletes and equine experts, resulting in inherent high emotional, physical and mental demands. Despite these demands, and reports of significant injury risk to those working in racing at ground level, there has been no research investigating the psychological risk factors for injury in UK racing stable staff and how psychological responses to injury may affect long term mental health and wellbeing. With mental health at the fore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 93 publications
0
6
0
Order By: Relevance
“…In both horseracing and equestrian sport, horsemanship skills are typically learnt in apprenticeship positions [ 20 ] and in deference towards those with greater equine experience [ 17 , 75 ], thus attitudes to injury are often ‘taught’ through peer-to-peer interaction [ 107 ]. This could suggest that whilst injury minimalization culture is a concern in horseracing [ 16 ], its prevalence and impact on injury reporting may be subject to individual yard microcultures, rather than a comprehensive industry-wide problem. Further research should consider the role of individual yard culture on injury reporting practices, and design educational intervention packages to reduce the stigma associated with injury and increase awareness of the implications of injury denial on employee health and wellbeing.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In both horseracing and equestrian sport, horsemanship skills are typically learnt in apprenticeship positions [ 20 ] and in deference towards those with greater equine experience [ 17 , 75 ], thus attitudes to injury are often ‘taught’ through peer-to-peer interaction [ 107 ]. This could suggest that whilst injury minimalization culture is a concern in horseracing [ 16 ], its prevalence and impact on injury reporting may be subject to individual yard microcultures, rather than a comprehensive industry-wide problem. Further research should consider the role of individual yard culture on injury reporting practices, and design educational intervention packages to reduce the stigma associated with injury and increase awareness of the implications of injury denial on employee health and wellbeing.…”
Section: Discussionmentioning
confidence: 99%
“…Employees who ignore their own health needs may experience higher levels of physical and mental stress, which can increase the risk of occupational injury and may impact the efficiency of the workforce [ 13 , 14 , 15 ]. Previous workplace stress research has reported increased mistakes due to lack of concentration or poor decision-making, slower completion of tasks and increased absenteeism [ 13 , 14 , 15 ], which could have an impact on the demands placed upon other staff, as well as potentially on the welfare of the racehorses if standards of care are not maintained [ 16 , 17 , 18 ]. The social demand for strict welfare standards in horseracing has led to a culture of ‘putting the horse first’ [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mental health can be defined as the "state of well-being in which the individual realizes his or her own abilities, can cope with the normal stresses of life, can work productively and fruitfully, and is able to make a contribution to his or her community" [4]. Concerns for racing staff mental health have already been reported; increased pressures due to a "relentless" fixture list [5][6][7], lack of work-life balance resulting in a reduced recovery time [5,6] and high rates of injury [8,9] have been identified as significant risk factors. An industry report suggested 72% of training yard staff experienced stress, anxiety, or depression in the prior 12 months [3].…”
Section: Introductionmentioning
confidence: 99%
“…Occupations with high physical and emotional pressure often have perceived assumptions that participants are physically and mentally strong [13], resilient and selfsufficient [14], and accustomed to working through pain [15], which, whilst required for the demands of the job [14], becomes problematic for mental health when those assumptions are challenged, for example due to injury [16]. Horseracing is a physically, mentally, and emotionally demanding occupation [9,17], and multiple risk factors have recently been identified that may increase the risk of injury for horseracing staff [8,9]. There is a high prevalence of injury in horseracing, with staff self-reporting an average of 3.3 injuries per annum [8].…”
Section: Introductionmentioning
confidence: 99%